A Live Detection of 500kVcircuit Breaker Found Defects and the Treatment - Zhang, Dewen; Qiu, Shuaihui; Shang, Fang; Han, Xiaoming; Gao, Siming; Yang, Jizheng (2025 IEEE 3rd International Conference on Image Processing and Computer Applications (ICIPCA), 2025)
In view of the defects in operation of 5111A pot-type circuit breaker in 500kV Heihe converter station, this paper expounds the ideas of spot defect inspection, defect cause analysis and defect treatment methods, etc., the improvement measures are put forward to eliminate the hidden trouble caused by the circuit breaker, and to ensure the safe and stable operation of the converter station.